A Market Risk Premium Problem: How should gold properties be valued on the Australian Securities Exchange? - Lloyd, Karen (Curtin University, 2021)
A mixed-method research approach was used to identify the market factors associated with gold project transactions on the ASX. Informed by the analysis of historical project transaction data an econometric model was developed through the triangulation of a quantitative study using capital markets theory and a qualitative study based on behavioural finance theory. The resulting valuation framework provides pragmatic guidance for use in research and industry practice.